Economic burden of pain in back and extremities in the adult population: a community-based estimate in rural Gadchiroli, India - Anand A. Bang; Shekhar Y. Bhojraj; Mahesh Deshmukh; Sameer Kalkotwar; Vinay R. Joshi; Tushar Yarmal; Abhay T. Bang (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Population-based estimates of economic burden due to pain in the back and extremities (PBE) are lacking from rural India. We aimed to estimate the burden by measuring the annual cost of: (i) medical consultation, (ii) purchasing medications, and (iii) work-days lost due to PBE in a rural adult population in Gadchiroli, India. # Methods This population-based recall study was conducted in two villages randomly selected from a cluster of 7 eligible villages in Gadchiroli district in India. All adults ≥20 years in these villages were surveyed by trained community health workers in January 2010 by making household visits. The data were collected using a structured, pre-tested questionnaire on the history of PBE and the consequent economic cost of pain during the previous 12 months. # Results Out of the 2535 eligible adults in two villages, 2259 (89%) were surveyed. Among these, 1876 (83%) had an episode of PBE in the preceding 12 months, 617 (27%) sought medical consultation and 1535 (68%) purchased medicines. Total expenditure in the study population (2259) over 12 months for PBE was 62,880 Indian Rupees, INR ($1298.6 at the annual mean currency conversion rate of $1 = 48.422 INR for the study year of 2009) on medical consultation and 855,203 INR ($17661.45) for purchasing medicines. Total 833 participants lost 24,205 work-days due to PBE. The mean work-days lost per adult participant were 11 days. The total estimated wages lost at the rate of 100 INR ($2.09) per day were 24,20,500 INR ($49987.6). The total cost of PBE in these two villages over 12 months was 33,38,583 INR ($68947.6) or 1317 INR ($27.19) per adult in the population. The mean annual economic loss due to PBE per symptomatic adult was 1789 INR ($36.94) which was 4.9% of the annual per capita income of 36286 INR ($725.72) for Gadchiroli in 2009-10. Women and the higher age groups were more likely to lose days at work due to PBE as well as experience higher out-of-pocket expenditure on treatment of PBE. # Conclusions This study showed substantial economic burden due to PBE in rural Gadchiroli. There is need to develop interventions to reduce the pain, loss of work-days and the out-of-pocket expenditure on medical consultation and purchasing medicines.